Introduced Fishmoths identified from South Atlantic Tristan da Cunha Island (Thysanura: Lepismatidae). - Hänel, Christine; Irish, John (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Two cosmopolitan Lepismatidae species found at Tristan da Cunha in the South Atlantic have been identified. These provide evidence that members of the Order Thysanura (Fishmoths or Silverfish) were imported to the Island. Thysanura do not feature amongst the naturally occurring insect faunas of the Tristan da Cunha archipelago or other islands to the south of it. In contrast, the presence of several Fishmoth species on St. Helena and Ascension Islands are noted in context of the geographical, political and social ties those Islands hold with Tristan da Cunha. Human mediation is known to be the key vector for the translocation of Fishmoths. In the Tristan scenario the increase in visitation frequency is regarded as a compounding factor. To combat the problems associated with alien imports to Tristan, a quarantine system needs to be implemented that is applied to all traffic embarking for entry into the territory. Keywords Thysanura, Lepismatidae, Lepisma, Ctenolepisma, Fishmoth, Silverfish, Tristan da Cunha, Gough Island, South Atlantic, introduction.